Chemical diagenesis in near-surface zone above oil fields in geochemical exploration; Applied Geochemistry; Vol. 95 - Sobolev I. S. Igor Stanislavovich; Bredikhin N. P. Nikolay Petrovich; Bratec T. Tatiana; Falk A. Yu. Alla Yurievna; Tolkachev O. S. Oleg Sergeevich; Rikhvanov L. P. Leonid Petrovich; Tishin P. A. Platon Alekseevich (2018, 2018)
Title screen